Penerapan Metode Balanced Scorecard Untuk Menilai Kinerja Perusahaan Pada PT Teknindo Geosistem Unggul - Ni Luh Ayu Atmi kamaratih; Achmad Maqsudi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2024)
This study aims to evaluate the performance of PT Teknindo Geosistem Unggul using the Balanced Scorecard method. Data sources consist of financial statements, number of employees, and secondary data from observations, documentation, and interviews. The results showed that the performance condition of PT Teknindo Geosistem Unggul if measured using a balanced scorecard on a financial perspective included in unhealthy conditions, on a customer perspective the results showed that overall, the level of customer satisfaction can be considered good, performance on the internal business perspective is in very good condition with new innovations and the company's quality management system including maintenance requests and improvements in after-sales service, The growth and learning perspective can be said to be in quite good condition which shows the results of a decrease in employee retention and an increase in employee productivity even though it had decreased in the previous year.